Sports fanaticism as a disease: a Corpus-based study of metaphors in Saudi newspapers - Mobarki, Yahya Abdu A.; Alzahrani, Fahad (Frontiers in Psychology, 2024)
Sports fanaticism in Saudi Arabia has become a kind of social concern in which fans of a particular sports team may practice hostile actions and aggressive behaviors towards fans of opposing teams. Saudi newspapers, overwhelmingly, associate sports fanaticism in Saudi sports with metaphors of disease. Informed by the discourse dynamics approach and metaphor-led discourse analysis, this research study considers how the use of disease metaphor in sports discourse portrays sports fanaticism to audiences. In specific, the aims are twofold: first, to show how decade-long newspaper articles have used the disease metaphor to address sports fanaticism in Saudi sports, and second, to understand the interpretations of the discursive use of such communicative devices. Utilizing King Abdulaziz City for Science and Technology Arabic Corpus (KACSTAC), this study examines a whole decade’s worth of newspaper articles (from 2010 to 2020). The findings of this research show that Saudi sports fanatics use and associate disease-related metaphors as vehicles to express intolerance. The findings also indicate that using disease metaphors in sports might have different meanings to fans. Some of these meanings may indicate acceptance of suffering, incomplete cures, and life threats in extreme cases and these all encourage patience.